Newly graduate nurses' experiences in the COVID-19 pandemic process and factors affecting their experiences: A mixed method study - Yeter Durgun Ozan; Ozlem Cicek; Esra Anus Topdemir (Medicine Science)
Nurses who started their professional lives during the coronavirus disease (COVID-19) pandemic have been exposed to significant levels of stress both in terms of being in a health chaos and in terms of their profession. This study aims to examine newly graduated nurses' experiences during the COVID-19 pandemic and explain the factors affecting their experiences. Mixed method design was used in the research. In the first stage of collecting quantitative data from 146 newly graduate nurses who started working during the pandemic. In the second stage, in which qualitative data were obtained, individual in-depth interviews were conducted with 15 newly graduate nurses using a semi-structured interview form over the Whatsapp application. Data collection took place from February to May 2021. The sources of stress were found to be; 88.4% fear of losing colleagues, 87.0% not being able to spend enough time with patients, 85.6% feeling inadequate, 85.6% increasing workload and fear of making mistakes, 81.5% colleagues getting sick, fear of losing and fear of infecting loved ones. Evaluation of quantitative data, number, percentage and mean test, thematic analysis method was used in the analysis of qualitative data. As a result of seven themes emerged from the thematic analysis: psychological impact, impact of heavy workload, effect of professional ambivalence feelings, social insensitivity, expectations that management was unable to meet, expectations from nursing educators, and positive profession-boosting effects of the pandemic. Findings demonstrate that newly graduate nurses who began their careers during a challenging time like the pandemic need to be strengthened, and their managers need to adapt and assist them in unusual circumstances. This study has yielded more robust evidence for the literature, thereby enriching the theoretical and practical discourse with more refined and comprehensive insights. It has provided lucidity on the uncertain experiences and their impacts on novice nurses. [Med-Science 2024; 13(4.000): 899-910]